After Virginia Tech: guns, safety, and healing in the era of mass shootings - Kapsidelis, Thomas P. (University of Virginia Press, 2019)
Prologue -- April 16, 2007 -- "Tragedy of monumental proportions" -- First steps -- "A deeper sense" -- When police call for help -- Accountability -- From a lifetime of silence -- "Back to day one" -- "Fire hose of suffering" -- Tower shadows -- "I will work this fight" -- The governor -- Texas half century -- Quiet carry -- Generations of advocacy -- The roads ahead -- April 16, 2017 -- Epilogue